Antibiotic resistance pattern of Streptococcus pneumoniae among infants younger than six months of age with acute otitis media in Erbil city - Muhsin Qarani, Sozan (Diyala Journal of Medicine, 2022)
Background: Acute otitis media (AOM) is one of the most common inflammatory disorders particularly in infants. Multiple factors such as gender, using bottle-feeding formula, and exposure to cigarette smoking are thought to raise the incidence of AOM. In infants at age six months or less, Streptococcus pneumoniae is the most common causative bacteria of AOM. The complications of pneumococcal infections are due to increasing the rate of antibiotic resistance among the S. pneumoniae strains that coincides with the increased use of antibiotics and multidrug resistant which severely limits the therapeutic options and poses a great threat to public health. Objective: To determine the antibiotic resistance patterns of S. pneumoniae in infants aged six months or less with AOM as the most frequently isolated bacterial pathogens and the most possible risk factors such as parent smoke and bottle feeding that may increase the incidence of acute otitis media in infants. Patients and Methods: A total of 148 infants six months of age or less, 87 males and 61 females with acute otitis media were enrolled in a current study. Swab from ear discharges were collected and cultured. The bacterial isolates were identified and the antibiotic susceptibility pattern for S. pneumoniae isolates was tested. Results: Among the 148 infants studied with acute otitis media, the frequency of the isolated microorganisms from infants with otitis media in male were higher than female and the majority of the infants were bottle feed and who exposed to cigarette smoke at home. S. pneumoniae was comprised the most frequent pathogen (40%) in the selected age, and the antibiotic resistance pattern of 68 S. pneumoniae isolates showed high resistance rate against penicillin, erythromycin and cefalothin. On the other hand, imipenem, vancomycin and chloramphenicol were the most effective drugs against S. pneumoniae isolates. Conclusion: The current study has identified S. pneumoniae as the most causes isolated pathogen in infants at age six months or less with acute otitis media and the majority of bacterial isolates showed a high rate of resistance against antibiotics and the majority of these isolates revealed multi drug resistance phenotype. It has been found that children exposed to passive smoking in the home and who are bottle-fed were at increased risk of acute otitis media .